The effect of company size, company growth, earnings growth, and capital structure on earnings response coefficient - Ratih Tri Indah Sari; Nuraini Rokhmania (The Indonesian Accounting Review, 2020)
Profit & Loss Statement becomes a consideration for investors in making stock transactions. Earnings response coefficient shows the attitude of an investor’s transaction in profit expectancy before or after the publication of the company’s financial statement. The purpose of this study is to examine factors that affect earnings response coefficient. The object of this research is consumer goods manufacturing companies listed on the Indonesia Stock Exchange during 2013-2017. The independent variables used are company size, company growth, earnings growth, and capital structure, while the dependent variable used is earnings response coefficient. The sampling technique used in this research is purposive sampling. Data analysis is done using multiple regression analysis. The results of this study show that earnings growth has a positive effect on earnings response coefficient, but firm size, firm growth, and capital structure have no effect on earnings response coefficient.